STARTEGI MARKETING PUBLIC RELATION PADA GENERASI MILENIAL DI PONDOK PESANTREN SUPERCAMP LA RAIBA HANIFIDA JOMBANG: STARTEGI MARKETING PUBLIC RELATION PADA GENERASI MILENIAL DI PONDOK PESANTREN SUPERCAMP LA RAIBA HANIFIDA JOMBANG - Fadlilah, Kusnul; Aditya Ramadhani, Reza; Rukmi Octaviana , Dila (LP2M IAI NURUL HAKIM, 2023)
This study aims to determine the marketing public relations strategy for the millennial generation at the La Raiba Hanifida Supercamp Islamic Boarding School. With the Marketing Public Relations strategy in Islamic boarding schools, it is still not optimal if only with an offline system because the target is currently 13-17 years old. The initial assessment carried out by the researchers at the La Raiba Hanifida Supercamp Islamic Boarding School, that the number of students was still small because in the field of public relations it was still in the process of development at the Islamic boarding school. Researchers used a descriptive qualitative research approach in digging up data. Based on the problems above, this research is to describe how the Marketing Public Relations strategy for the millennial generation at the La Raiba Hanifida Supercamp Islamic Boarding School. The results showed that the marketing public relations strategy of the millennial generation at the La Raiba Hanifida Islamic Boarding School in Jombang optimizes promotions through direct communication and indirect communication. By distributing brochures, as well as through social media. To carry out a marketing public relations strategy for the millennial generation at the La Raiba Hanifida Islamic Boarding School, Jombang. There are 7 Marketing Public Relations strategies (Publications, Media Identity, Events, news, speeches, participating in social activities, Sponsors).